História das casas de Goiânia, de 1930 a 1950: as faces contínuas e descontínuas do morar “erudito moderno” e do “morar ordinário” - Oliveira, Simone Borges Camargo de (2023)
This thesis emanates from a personal interest concerning human habitation, the locus of the “everyday experience of mankind”. It concentrates on concepts of "domicile," the "residence," and the act of "dwelling" – the commonplace inhabitation of the ordinary individual – together with the erudite inhabitation within the city of Goiania. The time frame is set between the 1930s and 1950s, in addition to studies up to the present time. Regarding the thesis relevance, despite previous meaningful work, goianiense historiography needs studies focusing on housing, the act of "dwelling” and new perspectives on habitation such as the one I am proposing. I intend to identify different social groups and the places of occupation of common “ordinary” houses – the segregated, informal city - and the erudite residences within the planned urban setting – the formal city. The dissertation is structured into three chapters. The first is dedicated to considerations that establish the theoretical foundation upon which the thesis is composed. The second has three sections: The initial one centers on the rhetorical discourse that legitimizes the capital shift. The second comments on the different aspects of the three plans within Goiania from 1933 to 1938, highlighting the correlation between dwelling typologies, territorial space, and its use, to understand the establishment of place and social group arrangements. The last one describes the typologies and architectural languages of public buildings and erudite houses built by the government for employees in the Central District, popular houses in the North District, and the ones built by private individuals. In addition, clarify the definition and classification of “Casas-Tipo”. The last chapter addresses ordinary common house considering modern city segregation. Furthermore, presents case studies from various locales to identify social groups and dwellings with discernible remnants in: Campinas, Worker’s Village-Campinas; the banks of Córrego Botafogo - Bota Fogo de Baixo (Vila Nova and Nova Vila Districs), East region; banks of Córrego Capim Puba, Northern Railway District. In writing the narrative, I developed numerous interpretative possibilities that unfold unexplored paths about the historiography of distinct modes of habitation among the residents of Goiania. To achieve this, I examined conceptual frameworks and documentary sources, where I encountered many publications concerning “erudite” residences. However, a comparable depth of information on popular houses, common individuals, and their ancestral knowledge is notably absent. I walk through several locations in the city searching for evidence of the common men, committing to deconstruct Goiás historiography to rebuild it. To achieve this, a specific methodology for this thesis is needed. Therefore, I conduct quasi-archaeological work by confronting primary imagery sources with primary written sources and the small signs left by these documents. I create mosaics and thus discover locations, types of buildings, and social groups. By this, I formulate four distinct study methodologies to identify the traces, the small gaps, which is the solution found for the process of collating the set of information that was obtained throughout the research